Transcriptome and Endogenous Hormones Reveal the Regulatory Mechanism of Flower Development in Camellia azalea - Xu, Jian; Yang, Fan; Nie, Ruimin; Zhao, Wanyue; Geng, Fang; Chen, Longqing (Plants (Basel), 2025)
Camellia azalea is an endemic species within the genus Camellia that exhibits the trait of summer flowering, which is of significant ornamental and research value. Nevertheless, research on the regulatory mechanisms of flower formation in C. azalea is still limited, so in this study, transcriptome sequencing and analysis of endogenous hormone contents were conducted at three distinct growth stages: floral induction, floral organ maturation, and anthesis. Illumina sequencing yielded a total of 20,643 high-quality unigenes. Comparative analyses of representative samples from the three growth stages identified 6681, 1925, and 8400 differentially expressed genes (DEGs), respectively. These DEGs were further analyzed for functional enrichment using the GO and KEGG databases. Additionally, core genes from each flowering pathway underwent expression pattern analysis and network diagram construction. This revealed that the flower development process in C. azalea is linked to the specific expression of the genes involved in the photoperiod, temperature, and autonomous pathways and is subject to comprehensive regulation by multiple pathways. Further analysis of the dynamic trends of five endogenous hormone contents and plant hormone signal transduction genes revealed significant differences in the requirements of endogenous hormones, such as gibberellins and indoleacetic acid, by C. azalea at distinct growth stages. Additionally, the majority of genes on the phytohormone signal transduction pathway demonstrated a high correlation with the changes in the contents of each hormone. The present study integrates physiological and molecular approaches to identify key genes and metabolic pathways that regulate the summer flowering of C. azalea, thereby laying a theoretical foundation for further investigations into its flowering mechanism and related functional genes.